Coconut Fibre As Stormwater Filters In Sustainable Urban Drainage Systems: A Systematic Review - Sankar, Siveraj (Universiti Sains Malaysia, 2021)
Bioretention systems are designed to remove both dissolved pollutants and particulate matter from stormwater runoff. This system is uses the functions of biofilters to retain water. Coconut fibre or coir is a natural fibre extracted from the outer husk of coconut. Various elements of the coconut tree (e.g. coir, shell, etc.) have been widely examined as biosorbents for the removal of various types of pollutants from water, making it one of the most important agricultural wastes studied as biosorbents for water treatment. Coconut fibre is a suitable material as a filter media in biofiltration or bioretention of stormwater in sustainable urban drainage system (SUDS). Hence, this study will attempt to review literature and gathering available experimental data and to investigate the characteristics, efficiency of coconut fibre in sustainable urban drainage systems. The use of coconut fibre filter for eliminating various pollutants from water and wastewater has a number of advantages, including high adsorption capacity for a variety of contaminants, good retention capacity and reduces peak discharge.